2021
DOI: 10.3390/nu13103600
|View full text |Cite
|
Sign up to set email alerts
|

Mother’s Milk Microbiome Shaping Fecal and Skin Microbiota in Infants with Food Allergy and Atopic Dermatitis: A Pilot Analysis

Abstract: The child microbiome, including gut and skin communities, is shaped by a multitude of factors, and breastfeeding is one of the most essential. Food allergy (FA) and atopic dermatitis (AD) are among the most common diseases in pediatrics, with the prevalence of each up to 6% and 20%, respectively. Therefore, we aimed at finding differences between the fecal and skin microbiomes of FA and AD patients in the context of breastfeeding, by means of the Illumina sequencing of 16S rRNA gene fragment libraries amplifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…The reduction of bifidobacteria in the human body and the increase of other bacteria have a certain relationship with the increase of age, but the bacteria that appear in different locations have different pathogenic properties [ 55 ]. With increasing age and gradual changes in eating habits, the intestinal microbiota in the human body will also change accordingly [ 56 , 57 ]. The influence of various factors changes the changes in the microbiota in the human body, and the composition of intestinal microbes will also be changed if drugs are used for treatment [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…The reduction of bifidobacteria in the human body and the increase of other bacteria have a certain relationship with the increase of age, but the bacteria that appear in different locations have different pathogenic properties [ 55 ]. With increasing age and gradual changes in eating habits, the intestinal microbiota in the human body will also change accordingly [ 56 , 57 ]. The influence of various factors changes the changes in the microbiota in the human body, and the composition of intestinal microbes will also be changed if drugs are used for treatment [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…As one of the most important sources providing the initial bacterial community, human breast milk is the optimal food for infants, while the feeding guidelines vary in different regions 177–179. Previous studies have confirmed the benefits of breast feeding for both mothers and infants 11 178 180 181. Through breast feeding, a variety of nutrients that are important in early life are transferred to infants (figure 4B).…”
Section: Microbial Transmission During and After Deliverymentioning
confidence: 95%
“…However, to our knowledge, no studies exist on the direct transfer of commensal skin bacteria to milk or breast tissue, and it remains unclear if microbial taxa can enter healthy nipple or areola tissue. On the other hand, human studies have shown that milk microbiomes are linked to variation in infant skin and gut microbiomes, which may be related to their incidence of allergy (Gołębiewski et al 2021).…”
Section: Milk Microbiome Formationmentioning
confidence: 99%